Assimilation and Difference: Two Recent Exhibitions of Archival Photographs - Cronin, J. Keri (Archivaria, 2002)
In this article, the author examines two recent Canadian archival exhibitions that explore the history of cultural interactions as depicted in the photographic record. She discusses how archival photographs are used both to educate viewers about critical aspects of Canadian society and events from Canada's past, and to encourage discussion of issues of cultural difference. The author considers the relevance of such exhibitions to present-day dialogues taking place on the same issues. RÉSUMÉ L'auteure fait la critique, dans cet article, de deux expositions d'archives récentes qui explorent l'histoire des interactions culturelles telles qu'illustrées par le biais de documents photographiques. Elle explique comment les photographies d'archives sont utilisées tant pour instruire les visiteurs sur certains aspects critiques de la société canadienne et sur les événements du passé que pour encourager des discussions sur les différences culturelles. L'auteure considère la pertinence de telles expositions dans le cadre du dialogue qui a cours actuellement sur ces questions.